Changing for the Better : The Path to Upper-Middle-Income Status in Uzbekistan - Trushin, Eskender; Carneiro, Francisco G. (World Bank, Washington, DC, 2015)
As a low-middle-income country with a gross domestic product (GDP) per capita of US$1,715 and a population of 30 million (nearly half of all of the Central Asian population), Uzbekistan has seen stable economic progress since the mid-2000s, both in terms of growth and poverty reduction. Growth has averaged 8 percent per year since 2004 and extreme poverty has declined from 27 percent in 2000 to 15 percent in 2012. Encouraged by this outstanding growth performance, the Uzbek authorities have set an ambitious goal for the country, to join the group of upper-middle-income countries by 2030. This note discusses the main challenges that the government is likely to face and the structural transformations that the economy will have to undergo to achieve this objective.